Functionalised exposed building materials: Self-cleaning, photocatalytic and biofouling abilities. Issue 13 (September 2017) - Tobaldi, D.M.; Graziani, L.; Seabra, M.P.; Hennetier, L.; Ferreira, P.; Quagliarini, E.; Labrincha, J.A.
Abstract: With the advent of urbanisation, there was a considerable and progressive worsening of urban air quality. Amongst the solutions proposed by scientific research, photocatalysis proved itself to be one of the most promising. In the present work, commercial glazed ceramic tiles were functionalised with a micrometric TiO2 layer adopting an industrial-like process. It was purposely chosen to avoid the use of nanoparticles because they might be inhaled and come into direct contact with the cells of the human organism during the industrial processing. Additionally, the self-cleaning, photocatalytic – the former by means of liquid-solid phase photocatalytic tests and water contact angle measurements; the latter against nitrogen oxides abatement – and biofouling abilities of the functionalised materials were thoroughly investigated. Results showed that the functionalised glazed ceramic tile possessed excellent self-cleaning and photocatalytic properties. As per the algal growth, surface roughness showed itself to be a key-point: the TiO2 surface layer, giving the material a higher surface roughness compared to the untreated one, had an accelerated algal growth process.